Analisis Faktor-Faktor yang Mempengaruhi Retensi Dokter dan Dokter Spesialis di RSUD Ragab Begawe Caram Kabupaten Mesuji: Suatu Pendekatan Kualitatif - Niesfu Syakhra; Iskandar Ali Alam; Habiburrahman Habiburrahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Doctor retention is a critical issue for regional hospitals in ensuring sustainable healthcare services. This study aims to analyze the factors influencing the retention of doctors and specialists at RSUD Ragab Begawe Caram, Mesuji Regency. A qualitative case study approach was employed, with data collected through in-depth interviews, observation, and document analysis. Data were analyzed using thematic analysis. The study is grounded in Herzberg’s Two-Factor Theory, Job Embeddedness Theory, and Social Exchange Theory. The findings indicate that doctor retention is influenced by both intrinsic and extrinsic factors. Intrinsic factors include work meaning, professional responsibility, and commitment to service, while extrinsic factors involve workload, incentive systems, work facilities, organizational support, and policy certainty. Doctor embeddedness is reflected through the dimensions of fit, links, and sacrifice, which are shaped by work relationships, environmental suitability, and personal considerations. Social and regional environmental conditions, such as access to facilities and distance from family, also affect doctors’ decisions to remain. The study concludes that intrinsic motivation plays a key role in doctor retention; however, it must be supported by adequate organizational systems and environmental conditions. Strengthening human resource policies, improving organizational support, and enhancing doctors’ welfare are essential to ensure sustainable retention in regional hospitals.